Oesophageal duplication cyst mimicking hydatid cyst in endemic areas - Akin, Melih; Erginel, Basak; Yildiz, Abdullah; Karadag, Cetin Ali; Sever, Nihat; Dokucu, Ali Ihsan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
The cystic appearance of both oesophageal duplications and pulmonary hydatid cysts can cause a misdiagnosis very easily due to rarity of cystic oesophageal duplications beside the higher incidence of hydatid cyst, especially in endemic areas. Here we report a 7-year-old girl with an oesophageal duplication cyst on the left side misdiagnosed as a hydatid cyst. The aim of the study is to report rare oesophageal duplications in the differential diagnosis of intrathoracic cysts.